2009
DOI: 10.1108/17542410910968814
|View full text |Cite
|
Sign up to set email alerts
|

Gender diversity in expatriation: evaluating theoretical perspectives

Abstract: PurposeThe purpose of this paper is to examine the range of theoretical underpinning used to explain women's participation as expatriates with a view to identifying the most promising theoretical lenses for future research.Design/methodology/approachDrawing upon theoretical explanations in the “women in management” and “women expatriates” literature, four main theoretical domains are identified that are used to understand and explain their continuing low representation as expatriates: women's choices, assignee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 69 publications
1
53
0
Order By: Relevance
“…The fact that women opt out of existing professional careers for their spouses/partners in the host country seems to automatically place them in a lower status category than their company transferred counterparts (Lee, et.al, 2009). The role of language in the expression of identity is of specific interest, especially considering the fact that women"s career choices are much more strongly influenced by their identity development than their male counterparts (Shortland, 2009).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…The fact that women opt out of existing professional careers for their spouses/partners in the host country seems to automatically place them in a lower status category than their company transferred counterparts (Lee, et.al, 2009). The role of language in the expression of identity is of specific interest, especially considering the fact that women"s career choices are much more strongly influenced by their identity development than their male counterparts (Shortland, 2009).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…The interviews also revealed the expanding technical and support roles available to military women, which has presented its own set of challenges as women assume leadership roles in non-traditional jobs. These findings provide further empirical support for research that women's home country context can impact on women's interest in and selection for international careers and perceived or real acceptance in host country contexts (see Hutchings et al, 2014;Shortland, 2009). …”
Section: Discussionmentioning
confidence: 52%
“…A twenty-five year meta-analysis of female expatriation conducted by Altman and Shortland (2008) reported that since Adler's work, three key trends have continued to be considered barriers to women's expatriation, namely: perceived resistance from the host country to accepting women in managerial roles; organizational resistance to selecting women and limited support when working internationally; and women's own disinterest in taking international assignments. Additionally, research has suggested that women's home country context can also impact on women's international careers with Shortland (2009) arguing home country prejudice in selecting women affects opportunities and it has been argued that social values suggesting women's primary commitment as care givers to immediate and extended family constrains their opportunities (see Hutchings et al, 2014).…”
Section: Female Expatriatesmentioning
confidence: 99%
“…Second, they are learning-driven assignments intended to drive individual career development and serve as a mechanism to transfer, share, and exchange knowledge between the expatriate and home country nationals. Most empirical studies of the social characteristics of corporate-transferee expatriates from the United States, Europe, and Japan derived from research by scholars of IHRM indicate these workers are predominately male, with men holding an average of 85 % of such positions across all industrial sectors, as much as 95 % in construction and engineering, and a relatively low 70 % in not-for-profit and charity employment (Shortland, 2009). tures (i.e., the dissemination of knowledge primarily from the corporate headquarters to subsidiaries) to the transnational mode, or the sharing and exchange of knowledge and staffing between all units of the firm (described by Bartlett & Ghoshal [1998] as the transnational form of the firm).…”
Section: Expatriation Global Talent and Knowledge Exchangementioning
confidence: 99%